Providing and Solving an Integrated Reverse Supply Chain Model of End-of-life Vehicles in Conditions of Uncertainty - Yousef Aghaeipour, Fatemeh Harsaj, Mahboubeh Sadeghpoor, Yadollah Rajaee (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Technology has provided new ways for languages, cultures and the world to be represented, expressed and understood. Nowadays, e-learning is being used more intensively. New approaches are involved with innovative pedagogical tools. Various fields of research can help us provide a new framework for educational tasks. In this paper we use two main fields of research, namely computational linguists and recommender systems to propose a new framework for e-learning. The implemented framework can be used for language learners to improve their language skills in an interactive scenario which automatically generates new questions and recommends the best items to each uses.